COPA3 peptide supplementation alleviates the heat stress of chicken fibroblasts - Siddiqui, Sharif Hasan; Khan, Mousumee; Park, Jinryong; Lee, Jeongeun; Choe, Hosung; Shim, Kwanseob; Kang, Darae (Frontiers in Veterinary Science, 2023)
Heat stress inhibits cellular proliferation and differentiation through the production of reactive oxygen species. Under stress conditions, antioxidant drugs promote stable cellular function by reducing the stress level. We sought to demonstrate COPA3 supplementation stabilizes fibroblast proliferation and differentiation even under heat stress conditions. In our study, fibroblasts were assigned to two different groups based on the temperature (control and heat stress) treatment. Each group was subdivided into two groups depending upon COPA3 treatment. Heat stress was observed to decrease the fibroblast viability and function and resulted in alterations in the fibroblast shape and cytoskeleton structure. In contrast, COPA3 stabilized the fibroblast viability, shape, and function. Moreover, heat stress and COPA3 were found to have contradictory actions with respect to energy production, which facilitates the stabilization of cellular functions by increasing the heat tolerance capacity. The gene expression levels of antioxidant and heat shock proteins were higher after heat stress. Additionally, heat stress promotes the mitogen-activated protein kinase/ extracellular signal-regulated kinase–nuclear factor erythroid 2-related factor 2 (MAPK/ERK-Nrf2). COPA3 maintained the MAPK/ERK-Nrf2 gene expressions that promote stable fibroblast proliferation, differentiation, and apoptosis. These findings suggest that COPA3 supplementation increases the heat tolerance capacity, viability, and functional activity of fibroblasts.